PESAN SIMBOLIK TRADISI SANDINGAN PADA MASYARAKAT PANDALUNGAN DI DESA JENGGRONG KECAMATAN RANUYOSO KABUPATEN LUMAJANG - Subahri, Bambang (Dakwah, 2018)
The tradition of Sandingan carried out from generation to generation by Pandalungan society is a combination of Javanese and Madurese Islamic culture which accomplishes symbolic message for the balance of macrocosm and microcosm which covers relation among human beings, humans and nature, and humans and the creators. This ritual is served by providing food and beverages on Monday, Thursday and Friday evenings started by burning incense and closed by reciting prayers aimed at the spirits of the ancestors.